2011
DOI: 10.3174/ajnr.a2378
|View full text |Cite
|
Sign up to set email alerts
|

Permeability Estimates in Histopathology-Proved Treatment-Induced Necrosis Using Perfusion CT: Can These Add to Other Perfusion Parameters in Differentiating from Recurrent/Progressive Tumors?

Abstract: BACKGROUND AND PURPOSE: Differentiating treatment effects from RPT is a common yet challenging task in a busy neuro-oncologic pratice. PS probably represents a different aspect of angiogenesis and vasculature and can provide additional physiologic information about recurrent/progressive enhancing lesions. The purpose of the study was to use PS measured by using PCT to differentiate TIN from RPT in patients with previously irradiated brain tumor who presented with a recurrent/progressive enhancing lesion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
25
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 30 publications
3
25
0
Order By: Relevance
“…Although a larger sample size is required to show consistent associations between OS and CT perfusion parameters across all time points, our results are consistent with previous reports that higher BV and PS are associated with poor outcomes [11,12,20,31,32]. It is also NEL non-enhancing lesion, CEL contrast-enhancing lesion; mo months, OS overall survival, BF blood flow, BV blood volume, PS permeabilitysurface area product, AUC area under the receiver operating characteristic curve a Parameters with sensitivities and specificities C70 % in stratifying OS when considering both grade III and IV glioma patients b Parameters with sensitivities and specificities C80 % in stratifying OS when considering both grade III and IV glioma patients noteworthy that while we showed significant hazards of death associated with both volumetric and CT perfusion parameters, only CT perfusion parameters resulted in sensitivities and specificities C70 % in stratifying OS while volumetric parameters did not.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Although a larger sample size is required to show consistent associations between OS and CT perfusion parameters across all time points, our results are consistent with previous reports that higher BV and PS are associated with poor outcomes [11,12,20,31,32]. It is also NEL non-enhancing lesion, CEL contrast-enhancing lesion; mo months, OS overall survival, BF blood flow, BV blood volume, PS permeabilitysurface area product, AUC area under the receiver operating characteristic curve a Parameters with sensitivities and specificities C70 % in stratifying OS when considering both grade III and IV glioma patients b Parameters with sensitivities and specificities C80 % in stratifying OS when considering both grade III and IV glioma patients noteworthy that while we showed significant hazards of death associated with both volumetric and CT perfusion parameters, only CT perfusion parameters resulted in sensitivities and specificities C70 % in stratifying OS while volumetric parameters did not.…”
Section: Discussionsupporting
confidence: 82%
“…CT perfusion has not been studied extensively despite the ubiquity of CT scanners [16]. However, CT perfusion can help distinguish between high and low grade gliomas [7,[17][18][19] and between tumor recurrence and radiation necrosis [20,21]. Therefore, CT perfusion should be considered as a potentially valuable perfusion imaging modality in neuro-oncology.…”
mentioning
confidence: 99%
“…CBV measures mainly microvascular attenuation, and f measures microscopic translational motions associated with microcirculation of blood. Similarly, Jain et al 13 reported that CBV showed a significant positive correlation with microvascular attenuation, whereas permeability parameter showed a significant positive correlation with microvascular cellular proliferation, which suggests that these perfusion parameters represent different aspects of tumor vessels. Moreover, spin-echo-based IVIM imaging has a substantially different vessel size sensitivity profile from that of gradient-echo-based DSC MR imaging.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the moderate PS observed in TIN is likely mediated by the release of VEGF in the pathogenesis of radiation necrosis [41]. In addition, susceptibility artefacts from blood products (hemorrhage, thrombus) and calcification can potentially complicate the analysis of DSC-MR studies while PCT is not affected by these artefacts [39,42].…”
Section: Differentiation Of True Progression From Post-treatment Effectsmentioning
confidence: 99%
“…Previous DSC-MR studies showed that true progression had significantly higher relative BV (rBV) than pseudoprogression [34,35] and TIN [36,37]. Using PCT, true progression showed significantly higher values of rBF, rBV, and PS than TIN [38][39][40]. Sensitivities and specificities of >80% were measured using PCT to differentiate true progression from TIN in brain tumors (Table 3).…”
Section: Differentiation Of True Progression From Post-treatment Effectsmentioning
confidence: 99%